Epidemiologia clássica e molecular da tuberculose pulmonar em pacientes da região norte de Minas Gerais - Prince, Karina Andrade de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Tuberculosis is a chronic infectious disease caused by the bacillus aerobic Mycobacterium tuberculosis. It causes health problems among millions of people each year, being ranked as the second leading cause of death from infectious disease worldwide. Thus, the aim of this study was to analyze the epidemiology of classical and molecular pulmonary tuberculosis in patients in North of Minas Gerais. We conducted an epidemiological study, an observational, longitudinal, retrospective and quantitative design. The population consisted of patients with suspected pulmonary TB, residents in the north of Minas Gerais patients at the University Hospital Clemente de Faria (HUCF), State University of Montes Claros (UNIMONTES), from January 2011 to December 2012. The clinical samples (sputum or bronchoalveolar lavage) of these patients were analyzed by Ziehl-Neelsen staining and culture by the method of Ogawa-Kudoh. Clinical isolates were subjected to molecular identification, genotyping by Spoligotyping techniques, RDRio, ERIC-PCR and MIRU-VNTR and drug susceptibility testing. The classical and molecular epidemiological correlation was performed using data from genotyping and classical epidemiological data. Of the 345 patients evaluated, 33 (9.6%) had the disease, with 69.7 % living in Montes Claros and 30.3 % in other cities in northern Minas Gerais. There was a prevalence of TB in males (75.8%), of mulattoes (60.6%), low education (42.4 %) and working age (78.9%) . The majority of new cases were (69.7%) and the smear was positive in 75.8 % of patients. The cure rate was low (30.3%) and high transfer (30.3 %). The most obvious grievances remain, the co -infection TB / HIV (6.1%) and alcoholism (24.25%) . Analysis of 33 clinical isolates by Spoligotyping allowed the identification of 22 different genetic profiles (66.7% genetic diversity). Among the genetic profiles found 15 (45.5%) LAM, 04 (18.2 %) belong to T family, 01 families (3.0%) to Haarlen ...

A tuberculose (TB) é uma doença infecciosa crônica causada principalmente pelo bacilo aeróbico Mycobacterium tuberculosis. Ela provoca problemas de saúde entre milhões de pessoas a cada ano, sendo classificada como a segunda causa de morte por uma doença infecciosa em todo o mundo. Assim, o objetivo desse estudo foi analisar a epidemiologia clássica e molecular da tuberculose pulmonar, em pacientes do Norte de Minas Gerais. Foi realizado um levantamento epidemiológico, de caráter observacional, longitudinal, retrospectivo e de delineamento quantitativo. A população foi composta por pacientes com suspeita de TB pulmonar, residentes na Região Norte de Minas Gerais, atendidos no Hospital Universitário Clemente de Faria (HUCF) da Universidade Estadual de Montes Claros (UNIMONTES), no período de janeiro de 2011 a dezembro 2012. As amostras clínicas (escarro ou lavado broncoalveolar) destes pacientes foram analisadas, através da técnica de Ziehl- Neelsen e da cultura pela método de Ogawa-Kudoh. Os isolados clínicos obtidos foram submetidos a identificação molecular, a genotipagem pelas técnicas de Spoligotyping, RDRio, ERIC-PCR e MIRU-VNTR e ao teste de susceptibilidade a fármacos. A correlação epidemiológica clássica e molecular foi realizada através dos dados da genotipagem e dos dados epidemiológicos clássicos. Dos 345 pacientes avaliados, 33 (9,6%) apresentavam a doença, sendo 69,7% residentes em Montes Claros e 30,3% em outras cidades do Norte de Minas Gerais. Houve predomínio da TB em indivíduos do sexo masculino (75,8%), da etnia parda (60,6%), de baixa escolaridade (42,4%) e em idade economicamente ativa (78,9%). A maior parte dos casos eram novos (69,7%) e a baciloscopia foi positiva em 75,8% dos pacientes. A taxa de cura foi baixa (30,3%) e a de transferência elevada (30,3%). Os agravos mais evidentes continuam sendo, a co-infecção TB/HIV (6,1%) e o alcoolismo (24,25%). A análise dos 33 isolados clínicos ...
Keywords: Tuberculose; Epidemiologia molecular; Pulmões - Doenças; Mycobacterium tuberculosis; Tuberculosis - Diagnosis